Re-thinking Social Protection Framework in Oil and Natural Gas Politics in Tanzania - Muya, Dominick K.; Dungumaro, Esther (Journal of Policy and Leadership, 2018)
Lack of a social protection framework to contain the inherent friction between African states and local communities over resource exploitation can either create or exacerbate the conditions for violent conflict. This article assesses the opportunities and challenges for implementing a social protection framework such as Local Economic Development (LED) plans for enhancing inclusive growth prospects. Southern regions of Lindi and Mtwara, in Tanzania are among impoverished areas characterised by the tension between the local community and the government over resource exploitation following the discovery of Oil and Natural Gas in those areas. The study relied on data obtained through the use of questionnaires and interview guides administered to stakeholders in Tanzania and secondary data analysis. Findings suggest several opportunities and barriers for the implementation of LEDs. In this light, the study has advanced a number of recommendations. Amongst them include reviewing country’s coherent policy guidelines and legislation to enhance equitable growth for the local populace, building supporting institutions at the local level for sustainability of LEDs, formulating Local Peace Committees in order to ensure the state of peace and security as well as maintaining the sustainability of investments.